Fact Sheet: The 2nd Annual NHEC California Minority Youth Environmental Training Institute - National Hispanic Environmental Council; Rodriguez, Juan (National Hispanic Environmental Council)
Fact sheet about the 2nd annual "California Minority Youth Environmental Training Institute". Topics covered: Origins of the program, day-by-day institute overview, application process/ selection, curriculum description, institute code of conduct, etc.